2019
DOI: 10.33023/jikep.v5i2.337
|View full text |Cite
|
Sign up to set email alerts
|

Expressive Writing Treatment Terhadap Stres Mahasiswa Di Prodi S1 Keperawatan

Abstract: Mahasiswa dalam tahapannya mengalami masa kritis dan transisi sebelum menjalani kehidupan sesungguhnya di masyarakat. Pada tahap ini mereka mengalami berbagai hal adaptasi dan tekanan dari lingkungan di sekitarnya. Penelitian ini bertujuan untuk menganalisis pengaruh expressive writing treatment terhadap stress mahasiswa. Desain dalam penelitian ini menggunakan metode deskriptif analitik dengan pre and post test control group design. Populasi penelitian ini adalah 152 mahasiswa Prodi s1 Keperawatan di semester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…It can be seen from the results of research by Retnoningtyas (2017) that the level of anxiety in the experimental group decreased significantly after being given treatment in the form of writing about positive and negative emotional experiences. Another study also revealed that giving treatment expressive writing therapy can reduce stress levels in students (Hatmanti, 2019). Expressive writing therapy is significantly able to help final-year students reduce anxiety levels and have good resilience or resilience.…”
Section: Philanthropymentioning
confidence: 94%
“…It can be seen from the results of research by Retnoningtyas (2017) that the level of anxiety in the experimental group decreased significantly after being given treatment in the form of writing about positive and negative emotional experiences. Another study also revealed that giving treatment expressive writing therapy can reduce stress levels in students (Hatmanti, 2019). Expressive writing therapy is significantly able to help final-year students reduce anxiety levels and have good resilience or resilience.…”
Section: Philanthropymentioning
confidence: 94%
“…Hasil penelitian yang sudah dipaparkan di atas sesuai dengan penelitian sebelumnya yang sudah dilakukan oleh (Hatmanti & Rusdianingseh, 2019) bahwa expressive writing dapat digunakan untuk menurunkan tingkat stres pada mahasiswa. Berdasarkan penelitian yang sudah dilakukan dan merujuk pada penelitian terdahulu.…”
Section: Aplication To the Selfunclassified